The effect of long-term fertilization on phosphorus content determined in different soil extractants on meadow chernozem soil - B. Szabó, Emese (Acta Agraria Debreceniensis, 2010)
The 0.01 M CaCl2 universal extractant is known all over Europe since the 90’s. During my research, I exam the phosphorus content determined in 0.01 M CaCl2 of the samples originated from the B 17 National Uniformed Long Term Fertilisation Trials in the experimental site Karcag, in the 40th year of the experiment. Relationships between the CaCl2-P and the AL-P content of the soil, the average yields, and the phosphorus balance of the2006/2007 year were studied. From the results of the study it was concluded as follows:– Correlation was close (r=0.68-0.7) between the AL-P and CaCl2-P. This is in accordance with the results of previous experiments in Hungary and other countries.– My studies confirmed that the calcium-chloride method indicates well the deficiency and the surplus of plant available phosphorus. In case of different degrees of negative balance, the amount of CaCl2 extractable phosphorus showed no changes, or decreased, and in case of positive balance it increased exponentially by the long-term effect of P rates.– The 120 and 180 kg ha-1 rates resulted in significant increases in the amount of CaCl2-P according to the control and treatments that are not fertilized with phosphorus. The 60 kg ha-1 rate didn’t result any increase as it didn’t meet the phosphorus requirement of winter wheat, and presumably the P-balance was negative in the earlier years as well.– It can be stated that the 0.01 M CaCl2 was able to assess the deficiency and the excess of phosphorus causing negative impacts on environment as well.